Depth-Differentiation and Seasonality of Planktonic Microbial Assemblages in the Monterey Bay Upwelling System - Reji, Linta; Tolar, Bradley B.; Chavez, Francisco P.; Francis, Christopher A. (Frontiers in Microbiology, 2020)
Coastal upwelling regions are hotspots of biological productivity, supporting diverse communities of microbial life and metabolisms. Monterey Bay (MB), a coastal ocean embayment in central California, experiences seasonal upwelling of cold, nutrient-rich waters that sustain episodes of high phytoplankton production in surface waters. While productivity in surface waters is intimately linked to metabolisms of diverse communities of Archaea and Bacteria, a comprehensive understanding of the microbial community in MB is missing thus far, particularly in relation to the distinct hydrographic seasons characteristic of the MB system. Here we present the results of a 2-year microbial time-series survey in MB, investigating community composition and structure across spatiotemporal gradients. In deciphering these patterns, we used unique sequence variants (SVs) of the 16S rRNA gene (V4–V5 region), complemented with metagenomes and metatranscriptomes representing multiple depth profiles. We found clear depth-differentiation and recurring seasonal abundance patterns within planktonic communities, particularly when analyzed at finer taxonomic levels. Compositional changes were more pronounced in the upper 0–40 m of the water column, whereas deeper depths were characterized by temporally stable populations. In accordance with the dynamic nutrient profiles, the system appears to change from a Bacteroidetes- and Rhodobacterales-dominated upwelling period to an oceanic season dominated by oligotrophic groups such as SAR11 and picocyanobacteria. The cascade of environmental changes brought about by upwelling and relaxation events thus impacts microbial community structure in the bay, with important implications for the temporal variability of nutrient and energy fluxes within the MB ecosystem. Our observations emphasize the need for continued monitoring of planktonic microbial communities in order to predict and manage the behavior of this sensitive marine sanctuary ecosystem, over projected intensification of upwelling in the region.